Our Experience in Chordee without Hypospadias: Results of 102 Cases - ERSÖZ, CEVPER; POLAT, Emre Can; ERDEM, Mehmet Remzi; TOPAKTAS, Ramazan; Ersoz, CEVPER; ONOL, Sinasi Yavuz (My University, 2014)
Purpose: We present long-term surgical experience of 102 chordee without hypospadias cases.